Pengaruh Kualitas Produk dan Lokasi terhadap Keputusan Pembelian Perumahan pada Shafira Residence Kediri - Ike Damayanti; Diana Ambarwati; Angga Permana Mahaputra (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the influence of product quality and location on housing purchase decisions at Shafira Residence Kediri. The research problem focuses on how product quality and location can affect consumers in making purchase decisions. This study employs a quantitative method with questionnaires distributed to respondents and data analysis conducted through validity tests, reliability tests, t-tests, F-tests, and multiple linear regression using SPSS 25. The results indicate that product quality has a significant partial effect on purchase decisions. This means that the better the quality of the product offered, the higher the consumer’s interest in purchasing a house at Shafira Residence. Similarly, the location variable shows a significant partial effect on purchase decisions, where accessibility and strategic positioning serve as key factors. Simultaneously, product quality and location significantly influence purchase decisions, with an F-test value of 10.727 (significance < 0.001) and a coefficient of determination (R²) of 0.671, indicating that the two independent variables explain 67.1% of the variation in purchase decisions. The conclusion of this study is that product quality and location are important factors influencing consumer purchase decisions at Shafira Residence Kediri. Therefore, developers need to improve housing product quality, ensure timely completion of construction, and enhance road access to the location in order to attract more consumers.